DEVELOPMENT OF AUGMENTED REALITY (AR) IPAS LEARNING MEDIA TO IMPROVE CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS - Najib, Muhammad; Suprihatiningrum, Jamil (IJIET (International Journal of Indonesian Education and Teaching), 2025)
This study aims to: 1) analyse the characteristics and quality of Class IV AR IPAS media products based on reviewer assessments; 2) implement AR IPAS media development products to improve the critical thinking skills of Class IV students; 3) analyze the effectiveness of AR IPAS media in improving critical thinking skills of Class IV students. The method used is the ADDIE RD model with the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, documentation, validation sheets, assessments, and tests. Data analysis was carried out using qualitative and quantitative descriptive techniques. The results showed that AR IPAS media integrates the real and virtual worlds, and provides interactive and real-time information in 2D and 3D, made with the Assemblr Edu application. This media is effective, easy to operate, and affordable to make. However, AR media is sensitive to changes in viewing angle and requires sufficient memory capacity on the device used. The implementation of AR IPAS media at SD Negeri Nanggulan and MI Al-Huda was conducted in five meetings, students were enthusiastic and actively involved, allowing direct concept exploration. AR IPAS media products are proven to be effective, proven through paired sample t-tests on two classes showing significance p 0.05, indicating a significant difference in students' critical thinking skills before and after using AR media.